2022
DOI: 10.3389/fmolb.2022.817517
|View full text |Cite
|
Sign up to set email alerts
|

Functional Micropeptides Encoded by Long Non-Coding RNAs: A Comprehensive Review

Abstract: Long non-coding RNAs (lncRNAs) were originally defined as non-coding RNAs (ncRNAs) which lack protein-coding ability. However, with the emergence of technologies such as ribosome profiling sequencing and ribosome-nascent chain complex sequencing, it has been demonstrated that most lncRNAs have short open reading frames hence the potential to encode functional micropeptides. Such micropeptides have been described to be widely involved in life-sustaining activities in several organisms, such as homeostasis regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 136 publications
0
15
0
Order By: Relevance
“…We expect translational repression mediated by CRISPRδ to have several advantages over preexisting methods. A wide array of studies have reported small but functional micropeptides encoded by long noncoding RNAs 157 , 158 , which were originally expected to contain no protein-coding regions. Moreover, mRNAs have been reported to have protein coding-independent functions 159 161 .…”
Section: Discussionmentioning
confidence: 99%
“…We expect translational repression mediated by CRISPRδ to have several advantages over preexisting methods. A wide array of studies have reported small but functional micropeptides encoded by long noncoding RNAs 157 , 158 , which were originally expected to contain no protein-coding regions. Moreover, mRNAs have been reported to have protein coding-independent functions 159 161 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that many conserved lncRNAs encode micropeptides. 40 For example, HoxB-AS1 was found to harbor two potential micropeptides of 15 and 61 amino acids, respectively. 30 However, in vitro translation assays for the corresponding mouse sequences did not detect any protein products from either of these two ORFs, which indicates that Hoxb3os is noncoding.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that mt-Shlp6 was found to be dynamically regulated in brown adipose tissue of the thirteen-lined ground squirrel across hibernation states ( Figure 4 ), the existence of ASncmtRNA-1 and ASncmtRNA-2 in hibernating model species and their abundance changes during daily torpor or the stages of hibernation are of special interest ( Burzio et al, 2009 ). They should also be analysed with regard to the finding that most long non-coding RNAs contain sORFs, hence, the potential to encode functional micropeptides ( Pan et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%